Analisis Boston Consulting Group (BCG) Pada Hotel Royal Senyiur Prigen Pasca Pandemi Covid-19 - Dellia Novandini; Yuliati Yuliati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The COVID-19 pandemic greatly impacted business activities, especially in the hospitality industry. One hotel which got an impact was the Royal Senyiur Hotel Prigen. Even though passing the pandemic era, it needs an appropriate strategy to survive and get back to normal in this transition stage. The research aims to reveal the BCG matrix quadrant position and the strategy implemented in the post-pandemic COVID-19. The research employed a case study to describe and conduct an in-depth analysis of a certain case. The qualitative data consisted of general terms and information on finding out something. The research used primary data from interviews with informants and secondary data from documentation. Based on the research result, Royal Senyiur Hotel Prigen has a market growth of 41.5%. Meanwhile, its relatif target markets were 1.21 and 1.27 times in 2022 and 2023, respectively. From the two calculations related to its market, the BCG matrix quadrant position is in Quadrant II, that is, Star with the strategy of hold.